Tissue tropisms, infection kinetics, histologic lesions, and antibody response of the MR766 strain of Zika virus in a murine model - Anna B. Kawiecki; E. Handly Mayton; M. Fausta Dutuze; Brad A. Goupil; Ingeborg M. Langohr; Fabio Del Piero; Rebecca C. Christofferson (Virology Journal, 2017)
Abstract Background The appearance of severe Zika virus (ZIKV) disease in the most recent outbreak has prompted researchers to respond through the development of tools to quickly characterize transmission and pathology. We describe here another such tool, a mouse model of ZIKV infection and pathogenesis using the MR766 strain of virus that adds to the growing body of knowledge regarding ZIKV kinetics in small animal models. Methods We infected mice with the MR766 strain of ZIKV to determine infection kinetics via serum viremia. We further evaluated infection-induced lesions via histopathology and visualized viral antigen via immunohistochemical labeling. We also investigated the antibody response of recovered animals to both the MR766 and a strain from the current outbreak (PRVABC59). Results We demonstrate that the IRF3/7 DKO mouse is a susceptible, mostly non-lethal model well suited for the study of infection kinetics, pathological progression, and antibody response. Infected mice presented lesions in tissues that have been associated with ZIKV infection in the human population, such as the eyes, male gonads, and central nervous system. In addition, we demonstrate that infection with the MR766 strain produces cross-neutralizing antibodies to the PRVABC59 strain of the Asian lineage. Conclusions This model provides an additional tool for future studies into the transmission routes of ZIKV, as well as for the development of antivirals and other therapeutics, and should be included in the growing list of available tools for investigations of ZIKV infection and pathogenesis.